Changes in the density of GFAP immunopositive cells in the brain of rats caused by a single prolonged stress - Ivaz, Sava (Medicinski podmladak, 2025)
Introduction: Post-traumatic stress disorder (PTSD) is a chronic syndrome caused by a traumatic stressful event. Many patients do not respond to conventional therapy, which shows that the pathogenetic mechanisms of PTSD are insufficiently known. PTSD is associated with anxiety, memory impairment, increased fear, and loss of hippocampal volume. Few studies have examined the role of glial cells in PTSD, while recent findings suggest that astrocyte pathology may be feature of the disorder. Single prolonged stress (PPS) is an animal model of PTSD consisting of mechanical restraint, forced swimming, and ether anesthesia until the tail reflex is lost. The Aim: To compare the density of astrocytes in the dentate gyrus, CA 1/2 and CA3 regions of hippocampus and medial prefrontal cortex (mPFC) of the brains of rats exposed to SPS compared to the control group. Material and Methods: Wistar rats (n=5) were exposed to PPS and sacrificed after 7 days in comparison with control animals (n=5). The density of astrocytes was determined by immunohistochemical staining of glial fibrillary acidic protein (GFAP). SSPS was used for statistical analysis. Results: The density of GFAP+ astrocytes in the hippocampus of rats exposed to PPS was statistically significantly reduced compared to the control group in the CA1/2 (p<0.01) and GD (p<0.05) regions, while no significant difference was observed in the CA3 region. The density of GFAP+ astrocytes was statistically significantly lower in mPFC region of rat brains treated by SPS compared to the control group (p<0.01). Conclusion: The results clearly indicate that SPS leads to significant reduction in density of astrocytes in hippocampus and mPFC, which suggests that changes in astrocytes may play a role in the development of morphological and functional disorders triggered by PTSD. Understanding the role of astrocytes in PTSD may contribute to development of new potential targets for treatment of disease.